-
Multiply both sides of the first equation by 12 at the same time to get 4x-3y=12, and multiply both sides of the second equation by 6 at the same time to get 3x+2y=12, and then solve the system of equations.
Multiply both sides of the second equation at the same time to get.
Add it to the first equation to get it.
x=30. y=12/17
-
x/3-y/4=1 ①
x/2+y/3=2 ②
12→ 4x-3y=12;③
6 → 3x+2y=12;④
obtained: x=5y; ⑤
Substituting gets: 3 5y+2y=12 y=12 17;
Substitute y=12 17 into :
x=5y=60/17;
x=60/17; y=12/17.
-
x/3-y/4=1
x/2+y/3=2
4x-3y=12 (1)
3x+2y=12 (2)
1)-(2) De:
x-5y=0
x=5y (3)
3) Substitution (1) gets:
20y-3y=12
17y=12
y=12/17
Solve the system of equations to obtain:
x=60/17
y=12/17
-
x^2+y^2=4 (1)
y=x-1 (2)
Replace Eq. (2) with Eq. (1).
x^2+y^2=4
x^2+(x-1)^2=4
Simplify. 2x^2-2x-3=0
x=(1+ 7) 2 or (1- 7) 2when x=(1+ 7) 2, y=(-1+ 7) 2when x=(1- 7) 2, y=(-1- 7) 2. (x,y)=(1+√7)/2,(-1+√7)/2) or ((1-√7)/2,(-1-√7)/2)
-
2(x-y)/3
x+y/4=-1
1)6(x+y)-4(2x-y)=16
2) Solution: 1) Multiply both sides of the equation by 12.
8(x-y)-3(x+y)=-12
Mergers of the same kind.
5x-11y+12=0
3) (2) Consolidation of similar items.
10y-2x-16=0
4) (3) * 2 + (4) * 5.
28y-56=0
So y=2 substituting y=2 into (1) gives x=2
-
1-3/4x
Move 3 4x to the right and 5 8 to the left, i.e.
3 4x because 1 = 8 8
So 1-5 8
So 3 4x
If x is on the denominator, then the denominator numerators on both sides are cross-multiplied to get: 12x=24, so x=2 If x is on the numerator, then the denominator numerators on both sides are cross-multiplied to get: 24x=12, so x=12 24=1 2
-
1-3/4 x=5/8
Solution: Subtract 1 from both sides of the equation to get.
1-1-3/4 x=5/8-1
3/4 x=-3/8
coefficient to 1, obtained.
x=1/2
-
2(x-4)+3(y+1)=16 to get 2x+3y=21 14(x-4)-7(y-1)=7 to get 4x-7y=16 21 x2-2 to get 13y=26 to get y=2
Substituting y=2 into 1, there is 2x+3x2=21, and the solution is x=15 2
-
The fractional equation is first multiplied by the least common multiple of the denominator on both sides, and then it is easy to solve the whole equation.
Formula 1: 2y-6x=17
Formula 2: 2x-y=3x+y 6 and then 12x-6y=18x+y is 6x+5y=0
Add to equation 1: 7y=17, y=17 7
x=-17/7*5/6=-85/42
Is the topic wrong, so troublesome.
-
3x-y+2=0, then y=3x+2. Bring in the second equation.
x 2 Heng Sui 16 + y 2 Hu Bao Qin 4 = 1 becomes.
x^2/16+(3x+2)^2/4=1
Multiply both sides of the equation by 16 at the same time to become a year.
x^2+4(3x+2)^2=16
Solution. x=0
y=2x=-48/37
y=-70/37
x2+y2+4x-2y-4=0, which is: (x+2) 2+(y-1) 2=9, which is a circle, the center of the circle (-2,1), and the radius 3 >>>More
From 3x-2y=5, we get the formula that represents y by x, y=(5-3x 2). >>>More
2x+2y=1 ①
6x-6y=1 ② >>>More
Question 15x-3y=2m
3x-5y=m-2 >>>More
The monotonic increase interval of the function y=sinx is (2k -1 2 , 2k +1 2 ), k is an integer, and the monotonic decrease interval is (2k +1 2 , 2k +3 2 ), and k is an integer. >>>More